Uji Organoleptik Pada Susu Biji Durian (Durio zibethinus Murr) serta Pemanfaatannya sebagai Media Pembelajaran - Nurmadina; Masrianih (Journal of Biology Science and Education, 2020)
Durian seed milk (Duriozi bethinus Murr) is processed from durian seeds which contains nutrients such as carbohydrates, fats, proteins, vitamins and minerals. This study aims to determine the level of public acceptance (organoleptic test) of durian seed milk. This research is a quantitative descriptive research. The object used is durian seeds made with 3 treatments, namely A1 (1 kg durian seeds + 1 liter of water), A2 (1 kg durian seeds + 2 liters of water) and A3 (1 kg durian seeds + 3 liters of water) with an assessment aspect namely aroma, taste, texture, and color. The results obtained show that durian seed milk has the highest organoleptic test value, namely in treatment A3 with an average hedonic scale value of 3.53 (likes) and treatment A2 with an average hedonic scale value of 3.33 (likes) while in treatment A1 the lowest with an average hedonic scale of 2.59 (somewhat like). The results of the study are very suitable to be used as learning media in the form of posters with a percentage of 82.48%, which is the average of the validation results of the three validators, namely content experts (70%), design experts (85.45%), media experts (92% ) and the results of the assessment by students (83.75%).